2014
DOI: 10.1002/adma.201400647
|View full text |Cite
|
Sign up to set email alerts
|

Azadipyrromethene‐Based Zn(II) Complexes as Nonplanar Conjugated Electron Acceptors for Organic Photovoltaics

Abstract: The effectiveness of new a electron acceptor for organic solar cells is demonstrated. The acceptor is a homoleptic zinc(II) complex of 2,6-diphenylethynyl-1,3,7,9-tetraphenylazadipyrromethene. The high power-conversion efficiency obtained is attributed to the acceptor's 3D structure, which prevents crystallization and promotes a favourable nanoscale morphology, its high Voc , and its ability to contribute to light harvesting at 600-800 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
101
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 29 publications
0
101
1
Order By: Relevance
“…We have shown that derivatives of Zn(ADP) 2 are promising electron acceptors for organic photovoltaics (OPVs) [910]. A series of zinc(II) derivatives with various pyrrolic substitutions showed power conversion efficiencies (PCEs) ranging from 2.2–4.1% when blended with poly(3-hexylthiophene) (P3HT), and the highest PCE was obtained with Zn(WS3) 2 , shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that derivatives of Zn(ADP) 2 are promising electron acceptors for organic photovoltaics (OPVs) [910]. A series of zinc(II) derivatives with various pyrrolic substitutions showed power conversion efficiencies (PCEs) ranging from 2.2–4.1% when blended with poly(3-hexylthiophene) (P3HT), and the highest PCE was obtained with Zn(WS3) 2 , shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A series of zinc(II) derivatives with various pyrrolic substitutions showed power conversion efficiencies (PCEs) ranging from 2.2–4.1% when blended with poly(3-hexylthiophene) (P3HT), and the highest PCE was obtained with Zn(WS3) 2 , shown in Fig. 1 [910]. In comparison, free ligands and BF 2 + chelates showed negligible power conversion efficiencies, and Zn(ADP) 2 gave a maximum efficiency of 1.4% [11].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with fullerene acceptors, nonfullerene acceptors present some advantages, such as broad and strong absorption, adjustable LUMO energy levels, and long‐term stability. In recent years, FF‐OSCs developed quickly21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42 and achieved PCEs of up to 6.8% 25…”
mentioning
confidence: 99%
“…In recent years, there has been signi-cant advancement in small-molecule-based non-fullerene acceptors for OSCs. [37][38][39][40][41][42][43][44][45] We note that our objective in this work is to investigate the impact of small structural differences on device performance, rather than to achieve the state-of-art PCE. Before an OSC device was fabricated, uorescence quenching experiments were conducted to determine the optimum ratio between P3HT and BTD-P compounds.…”
Section: Application To Organic Solar Cell As Electron Acceptorsmentioning
confidence: 99%